From transcendental egology to orientation theory: Toward a mereological foundation for the different senses of the “self” in conscious experience - Guardiola, Joan González (Frontiers in Psychology, 2022)
In the present work we want to make a contribution to the origins of the notion of "minimum self" in Husserl's phenomenology. Starting from the difference between philosophy of the Subject and philosophy of the Self, the aim of our research is to show that the Cartesian association between both philosophies would not correspond exactly to the conception of the Self as we find it in Edmund Husserl’s works. With this, we intend to nuance Heidegger's accusation of Husserl's "Cartesianism". At the same time, we show how a detailed analysis of the "senses of the Self" in Husserl's phenomenology already allows us to extract the notion of "minimal Self" as it has been introduced in the debate, very lively and current, between psychiatry and phenomenology. In our research we also show that, in order to move the theory of the transcendental Ego towards the theory of the orientation of the life of consciousness, it is necessary to consider the foundation of the concepts of the Ego in the technical vocabulary of the formal mereology of the 3rd husserlian “Logical Investigation”.